Comparative studies and 'cross-national attraction' in education: a typology for the analysis of English interest in educational policy and provision in Germany - Ochs, K; Phillips, D (2002)
This paper describes a 'structural typology' to assist in the analysis of ways in which policy-makers in one country explore educational provision in another and seek to 'borrow' from it. In this analysis we look specifically at England's 'cross-national attraction' to education in Germany over the past 200 years. The paper aims to provide an analytical programme to use in comparative education and to facilitate exploration of the importance of context in shaping educational phenomena.